Citrate Root Exudation under Zn and P Deficiency (JOURNAL OF TROPICAL SOILS, 2013)
Zinc and phosphorus are essential nutrients with low bioavailability in calcareous soils. Some plants exude organicacids to increase the solubility of these two nutrients. The objective of this study was to examine citrate exudation rates of different lupin (Feodora and Energy) and rapeseed (Dunkeld, Yickadee and Rainbow) cultivars under deficiencies of Zn and P. The plants were cultivated into three different nutrient solutions (complete, -Zn, and -P) with pH around 7. Under Zn deficiency, rapeseed cultivars lost about 80% of its shoot fresh weight, but the roots did not exude any organic acids such as citrate, malate or oxalate. Both lupin and rapeseed cultivars exuded citrate onlyunder phosphorus deficiency. The exudation rates of Feodora and Energy were 3.89 μmol g-1 RDW h-1 and 3.45 μmol g-1 RDW h-1, respectively, while that of Dunkeld was 15.1 μmol g-1 RDW h-1. The results indicated that lupin and rapeseed lost their production under Zn deficiency but they did not exude organic acid, while under P deficiency both plants exuded citrate.Keywords: Citrate; deficiency; exudation rate; lupin; phosphorus; rapeseed; Zn[How to Cite: Siane BAE. 2012. Citrate Root Exudation under Zn and P Deficiency. J Trop Soils, 17 (3) : 219-225. doi: 10.5400/jts.2012.17.3.219][Permalink/DOI: www.dx.doi.org/10.5400/jts.2012.17.3.219]
Keywords: Citrate; deficiency; exudation rate; lupin; phosphorus; rapeseed; Zn